Grzimek’s Student Animal Life Resource: Crustaceans, Mollusks, and Segmented Worms - Evans, Athur (The Gale Group, Inc, 2011)
Grzimek's Student Animal Life Resource: Crustaceans, Mollusks and Segmented Worms offers readers comprehensive and easy-to-use information on Earth's animals. Entries are arranged by taxonomy, the science through which living things are classified into related groups. Each entry includes sections on physical characteristics; geographic range; habitat; diet; behavior and reproduction; animals and people; and conservation status. Family entries are followed by one or more species accounts and a range map and photo or illustration for each species. Entries conclude with a list of books, periodicals, and Web sites that may be used for further research.